Efficacy of high-power laser therapy combined with exercise on wrist pain, function and joint position sense in female gymnasts with non-specific chronic wrist pain - Morsi Galal , Dina Othman Shokri; Abd-Elfattah, Hanaa Mohsen; Sakr, Hend Reda; Elserty, Noha; Elias, Mina Atef Georgui (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
Background: Wrist pain is common and debilitating among gymnasts, presenting a tricky diagnostic and therapeutic challenge resulting in falling down in training sessions and during performance. Objective: To find out the effect of high-power laser treatment, either alone or in combination with exercise, on wrist pain, function and joint position sense in female gymnasts with non-specific chronic wrist pain. Methods: Thirty-six female gymnasts (aged 10 to 16 years) who were diagnosed with non-specific wrist pain were recruited as the participants for the study, and were randomly allocated into three groups. The participants of the laser therapy group received only high power laser therapy, the exercise program group participants received exercises only, and the participants of the combined therapy group received both laser and exercises. Pain, function, and joint position sense were the outcomes measures in the study. Results: In all treatment groups, all measured results improved after therapy. The laser therapy group had the least significant impact, whereas the combined therapy group had the most significant impact. Conclusion: It might be early to say whether solely high-power laser therapy is an effective non-invasive modality for treating female gymnasts with non-specific chronic wrist pain. The addition of associated co-interventions to high power laser treatment can improve the beneficial effects of laser therapy.